New insights about Quercus faginea (s.l) taxonomic status in northern Africa - Aissi, Abdeldjalil (Mediterranean Botany, 2023)
The genus Quercus is known for its taxonomic complexity that is characterized by the abundant morphological diversity and phenomena of hybridization and introgression found in a number of its species. The number of taxa continues to change and evolve despite systematists’ attempts to clarify and simplify it. The Quercus faginea s.l. complex represents one of the most conclusive and complex examples found in the North-Western Mediterranean and North Africa. Nevertheless, the systematics of this complex have undergone a remarkable evolution from the first Lamarckian taxa Q. lusitanica and Q. faginea to the present day, especially in the Iberian Peninsula, Tunisia, and Algeria, by virtue of the recognized taxa. To compare Moroccan taxa with those found in other regions, as well as update the taxonomic status of populations found in Morocco, data found in a corresponding bibliography was used for a critical and objective analysis. Although the taxonomic situation remains unresolved, the analysis found that there is a likely presence of the faginea variety in Morocco, while also anticipating the confirmation of a new morphological analysis that accounts for the stable criteria used for an infraspecific distinction. The rest of Morocco’s stands seem to be represented by Q. canariensis and Q. faginea subsp. broteroi. Considering the uncertain existence of maroccana, further study of its distinct morphological and biogeographical peculiarity is required.